Molecular determinants regulating selective binding of autophagy adapters and receptors to ATG8 proteins - Martina Wirth (Nature Portfolio, 2019)
Autophagy adaptors and receptors contain LC3-interacting region (LIR) motifs that bind selectively to the LIR docking site of GABARAP and other members of the ATG8 family. Here the authors show that in addition to the LIR motif also the region C-terminal of it is important for the binding specificity of both the centriolar satellite protein PCM1 and the ULK1 complex to GABARAP subfamily proteins.